In regard to “Tran A, Zhang J, Woods K, Yu V, Nguyen D, Gustafson G, Rosen L, Sheng K. Treatment planning comparison of IMPT, VMAT and 4π radiotherapy for prostate cases. Radiation oncology. 2017 Jan 11; 12(1):10” - Sarkar, Biplab (Radiation oncology (London, England), 2018)
This article describe the three dimensional geometrical incompetency of the term "4π radiotherapy"; frequently used in radiation oncology to establish the superiority (or rather complexity) of particular kind of external beam delivery technique. It was claimed by several researchers, to obtain 4π solid angle at target centre created by the tele-therapy delivery machine in three dimensional Euclidian space. However with the present design of linear accelerator (or any other tele-therapy machine) it is not possible to achieve more than 2π with the allowed boundary condition of 0 ≤ Gnatry position≤π and [Formula: see text]≤Couch Position≤[Formula: see text] .This article describes why it is not possible to achieve a 4π solid angle at any point in three dimensional Euclidian spaces. This article also recommends not to use the terminology "4π radiotherapy" for describing any external beam technique or its complexity as this term is geometrically wrong.